Syphilis mimicking primary biliary cholangitis (Research, Society and Development, 2025)
Introduction: Syphilitic hepatitis can be defined as a cholestatic pattern of elevated enzymes with treponemic serological evidence, when there is an absence of alternative causes of hepatic aggression. Infections are considered important environmental factors that contribute to decreased tolerance to autoantigens, which can trigger autoimmune diseases. The aim of this article is to report a case in which syphilis mimicked the clinical picture and laboratory findings of primary biliary cholangitis, an autoimmune cholestatic disease. Case report: a 20-year-old man, immunocompetent, admitted with nausea, pruritus, jaundice, choluria, fecal acolia, inappetence, vomiting, fever, chills, epigastric pain and weight loss for about 20 days. Laboratory exams showed hyperbilirubinemia at the expense of direct bilirubin and elevated liver enzymes with a canalicular pattern, VDRL reagent 1/256, antimitochondria 1/80. After eradication of Treponema with benzathine penicillin, the patient developed complete recovery of the clinical picture, an important decrease in VDRL (1/4), disappearance of autoantibody and complete biochemical normalization. Conclusion: The present case highlights the importance of properly performed anamnesis, physical examination and adequate follow-up until the response or not to treatment, to confirm the diagnosis. It is important to include secondary syphilis among the possible causes of liver disease.